2023
DOI: 10.1002/cncr.34645
|View full text |Cite
|
Sign up to set email alerts
|

Psychological mobile app for patients with acute myeloid leukemia: A pilot randomized clinical trial

Abstract: Background Patients with acute myeloid leukemia (AML) experience a substantial decline in quality of life (QoL) and mood during their hospitalization for intensive chemotherapy, yet few interventions have been developed to enhance patient‐reported outcomes during treatment. Methods We conducted a pilot randomized trial (ClinicalTrials.gov identifier NCT03372291) of DREAMLAND, a psychological mobile application for patients with a new diagnosis of AML who are receiving intensive chemotherapy. Patients were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
1
0
Order By: Relevance
“…In short, self-care significantly influences changes in the social support variable and increases it, ultimately leading to an improvement in the quality of life of the elderly. This conclusion is corroborated by other related prior research (Ahmadi & Valizadeh, 2021;Ardouin et al, 2023;Badpar et al, 2019;El-Jawahri et al, 2023;Ferrari et al, 2017;Fung et al, 2021;Lindsay et al, 2011;Maddi, 2015;Moulaei et al, 2022;Park et al, 2021;Saeidi et al, 2021;Zal et al, 2022), which validate and confirm the findings of this research.…”
Section: Discussionsupporting
confidence: 91%
“…In short, self-care significantly influences changes in the social support variable and increases it, ultimately leading to an improvement in the quality of life of the elderly. This conclusion is corroborated by other related prior research (Ahmadi & Valizadeh, 2021;Ardouin et al, 2023;Badpar et al, 2019;El-Jawahri et al, 2023;Ferrari et al, 2017;Fung et al, 2021;Lindsay et al, 2011;Maddi, 2015;Moulaei et al, 2022;Park et al, 2021;Saeidi et al, 2021;Zal et al, 2022), which validate and confirm the findings of this research.…”
Section: Discussionsupporting
confidence: 91%
“…The results in our study mirror the findings of others related to the association between smartphone app use and QoL in young patients with cancer. The pilot randomized clinical trial by El-Jawari et al [ 37 ] found that their psychological smartphone app for young, newly diagnosed patients with acute myeloid leukemia showed significant improvement in QoL (Functional Assessment of Cancer Therapy-Leukemia) and self-efficacy (Cancer Self-Efficacy Scale) and a decrease in symptom burden (Edmonton Symptom Assessment Scale) in patients using the smartphone app compared to the patients receiving standard care. Additionally, the meta-analysis by Siew et al [ 38 ] demonstrated that social media–based interventions significantly improved QoL and anxiety symptoms among patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire questions assess the individual's confidence in performing self-care tasks, and the total score ranges from 29 to 145. This tool is self-reported and its internal consistency was reported using Cronbach's alpha as 0.94 (El-Jawahri et al, 2023;Soleymany & Sarifi, 2023).…”
Section: Self-carementioning
confidence: 99%
“…Research results indicate that having a psychological program in cancer patients is significantly related to selfcare, increased efficiency, symptom improvement, and life quality (El-Jawahri et al, 2023).…”
Section: Introductionmentioning
confidence: 99%